ҲӘЗИРГИ РУС ҲӘМ ҚАРАҚАЛПАҚ ТИЛЛЕРИНДЕ БИРГЕЛКИЛИ ҚУРАМЛЫ ДӘНЕКЕРСИЗ ҚОСПА ГӘПЛЕРДИҢ ГЕЙПАРА ТЕОРИЯЛЫҚ МӘСЕЛЕЛЕРИ - Халмуратов, Т.Ж. (FAN va JAMIYAT, 2024)
The article discusses some theoretical issues of a non-union complex sentence of homogeneous composition in the Russian and Karakalpak languages.